Current understanding and management of clostridioides difficile infection: an overview - Paudel, Rama (International Journal of Research in Medical Sciences, 2023)
Clostridiodes difficile infection (CDI) is a major cause of healthcare-associated infections worldwide, with a significant morbidity and mortality. The incidence of this infection has been increasing in recent years, particularly among elderly patients and those with comorbidities. The pathogenesis of CDI involves the disruption of the gut microbiota, followed by the production of toxins that lead to colonic inflammation and tissue damage. The clinical presentation varies from mild diarrhea to severe pseudomembranous colitis, toxic megacolon, and sepsis. The diagnosis of CDI is based on the presence of clinical symptoms, laboratory testing, and imaging studies. The treatment of CDI involves antimicrobial therapy, supportive care, and infection control measures. Recently, there have been significant developments in the management of CDI, including the use of fidaxomicin, fecal microbiota transplantation (FMT), and monoclonal antibodies. This manuscript reviews the epidemiology, pathogenesis, clinical presentation, diagnosis and updated guidelines for the management of CDI.